2009
DOI: 10.3201/eid1506.081126
|View full text |Cite
|
Sign up to set email alerts
|

Hantaviruses in Rodents and Humans, Inner Mongolia Autonomous Region, China

Abstract: Vigilance is needed to prevent hemorrhagic fever renal syndrome caused by Hantaan and Seoul viruses in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…The most likely cluster was found at Yiyuan County in October to December 2012, and the secondary cluster was detected at the centers of Zibo City in May to June 2009. Previous studies reported that the transmission of HTNV through Apodemus agrarius peaked in the winter, while Rattus norvegicus associated SEOV infections mainly occurred in the spring [6], [8], [9], [33]. Thus, the human infections in the most likely cluster in the fall and winter reflect a seasonal characteristic pattern of HTNV transmission, and a seasonal characteristic of SEOV transmission in the secondary cluster.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The most likely cluster was found at Yiyuan County in October to December 2012, and the secondary cluster was detected at the centers of Zibo City in May to June 2009. Previous studies reported that the transmission of HTNV through Apodemus agrarius peaked in the winter, while Rattus norvegicus associated SEOV infections mainly occurred in the spring [6], [8], [9], [33]. Thus, the human infections in the most likely cluster in the fall and winter reflect a seasonal characteristic pattern of HTNV transmission, and a seasonal characteristic of SEOV transmission in the secondary cluster.…”
Section: Discussionmentioning
confidence: 84%
“…Occurrence of HFRS cases is seasonal with a bimodal pattern and studies suggest that the pattern is linked to varying transmission dynamics of the two serotypes of hantaviruses among their animal hosts. HTNV-caused HFRS cases occur year-round but tend to peak in the winter while SEOV-caused infections typically peak in the spring [6], [8], [9]. Hantaviruses are primarily transmitted from rodent host to human by aerosols generated from contaminated urine and feces and possibly from contaminated food or rodent bites [10]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [2007] reported that seaport might be a source of hantavirus spread. Recently, it was found that the HFRS emerged in Bayannaoer district of Inner Mongolia might be caused by SEOV imported from the neighboring HFRS endemic areas [Zhang et al, 2009b]. Up to date, SEOVs have been found worldwide [McCaughey et al, 1996;Heyman et al, 2004Heyman et al, , 2008Easterbrook et al, 2007;Cueto et al, 2008;Weissenbacher et al, 1996;Wang et al, 2000;Reynes et al, 2003;Shi et al, 2003;Plyusnina et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…cDNA of the Small (S) and Medium (M) segments of the hantavirus genome was prepared with AMV transcriptase (Promega, Beijing, China) in the presence of primer P14 [19]. Partial or complete sequences of the S and the M segments were amplified as described previously [10], [20], [21]. All voles and insectivores were also screened for hantaviruses using RT-PCR as described previously [22].…”
Section: Methodsmentioning
confidence: 99%